Resiliensi Guru PAUD Ditinjau Dari Regulasi Emosi, Usia Dan Masa Kerja Pada Sekolah Inklusi - Alucyana; Yenni Yunita; Restu Nabila; Ria Safitri; Syarifah Fahriah (UIN Sultan Maulana Hasanudin Banten, 2024)
This research examines the resilience of PAUD teachers in terms of emotional regulation, age and years of service in inclusive schools. The aim of this research is to analyze a teacher's regulation in terms of emotional regulation, the teacher's age and the teacher's length of service. This type of research is quantitative correlational. This approach is included in the correlational category because this research looks for whether there is a relationship between one variable and another variable and if there is a relationship then we look for the extent of the relationship between the variables. The variables in this research consist of Resilience and Emotional Regulation, Age and Years of Work. The sample in this research was 60 people. The data analysis method used is multiple regression. The research results found that emotional regulation, age and years of service had a significant effect on the resilience of PAUD teachers, 75.1% of the resilience of preschool teachers was influenced by emotional regulation, and 75.1% of age influenced the resilience of PAUD teachers in inclusive schools. It is hoped that future researchers will be able to develop the resilience of PAUD teachers in inclusive schools from other aspects. This article describes the activities of practicum batik in early childhood early childhood is age 6-8 years. Methods of this action research using a combined method that is using qualitative methods and quantitative methods. The action research model used is the Kemmis and Taggart model. Research data obtained from observation and interview. The results of this study indicate an increase in the creativity of children through the practice of batik “tulis” and batik “jumputan” (tie dye). Playing activities and interests of children on the practice of batik, is a capability that is characterized by four aspects of creativity: fluency, flexibility, originality, and elaboration.